The Influence of Algorithm-Based Advertising on Social Media on Millennial Consumer Behavior - Apriansyah, Ade; Gunarto, Muji; Helmi, Sulaiman (Asian Journal of Management Analytics, 2025)
This study aims to analyze the influence of algorithm-based advertising on social media on millennial consumer behavior. Algorithm-based advertising uses consumer behavior data to present relevant content, so it has great potential to influence purchase decisions. This research was conducted with a quantitative approach through a survey of millennial respondents who actively use social media. The results showed that the relevance of ads, display frequency, and trust in social media platforms had a significant relationship with consumer behavior. Recommendations are given for the optimization of algorithm-based marketing strategies.